Penanaman Tanaman Obat Keluarga (Toga) - Yessi Azwar; Novi Yanti; Doni Hendra; Eva Santi; Noviyanti Noviyanti; Iyang Maisi (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Indonesia has a very high biodiversity, so it is rich in various medicinal plants that have the potential to be developed and utilized optimally. The phenomenon of society in general is that the use of generic drugs is more effective in treating disease than consuming medicinal plants. The use of medicinal plants is considered ancient and does not provide significant results. Times have started to change where conventional medicine has become a luxury for some people, so traditional medicine through Family Medicinal Plants (TOGA) is starting to be glimpsed by some people in Indonesia. The community partnership program has the aim of increasing community understanding and skills through socialization of the use of TOGA to create a healthy community in Rumbai hill village. There are 3 main components that are discussed in the understanding and skills of the community including: understanding the types of TOGA, understanding the efficacy/benefits of TOGA plants, and being able to practice how to process TOGA. The problem in society is that there are still few people who empower their home yards to plant toga plants. The purpose of this community service is to increase the knowledge of PKK mothers about the types of TOGA, the benefits/benefits of TOGA, and to show the procedures for planting TOGA with limited land. The method used is lecture, demonstration and discussion and question and answer. The result of this service is that the community has used the yard of the house to be planted with toga plants.